مقارنة سريرية للتخدير الموضعي خلف المقلة مع التخدير حول المقلة في عمليات الساد خبرة مشفى الأسد الجامعي للعام 2007 - تعتاع, عبد القادر; يوسف, حبيب; إمام, سامي (Latakia University Journal -Medical Sciences Series, 2019)
تم تقييم 32 مريضا أجري لهم جراحة ساد خارج المحفظة مع زرع عدسة في دراسة مستقبلية عشوائية للمقارنة بين التخدير خلف المقلة و التخدير حول المقلة. قسم المرضى إلى مجموعتي دراسة و تم تقييمهم اعتمادا على ثلاثة معايير مهمة في الجراحة العينية، التخدير الحسي و شل حركة المقلة و كفاية مدة التخدير. أظهرت النتائج أن فعالية التخدير حول المقلة كانت مشابهة لفعالية التخدير خلف المقلة في كل من المعايير الثلاثة، و كون التخدير حول المقلة يطبق خارج المخروط العضلي فإن إمكانية حدوث اختلاطات متعلقة بالعصب البصري أو الجهاز العصبي المركزي أو كرة العين تكون قد تقلصت. Thirty two patients having extracapsular cataract surgery with IOL transplantation were evaluated in a prospective randomized study comparing retrobulbar and peribulbar anaesthesia. Patients were divided into two study groups and evaluated on three critical criteria in ophthalmic surgery, namely: sensory anaesthesia, akinesia and sufficient anaesthesia period. The results showed that the efficacy of the peribulbar block was similar to that of the retrobulbar block for all three criteria. Because peribulbar anesthetic is administered outside the muscle cone, the potential for optic nerve, central nervous system and eye ball complications should be minimized.